Achievement of guideline-based lipid goals among very-high-risk patients with atherosclerotic cardiovascular disease and type 2 diabetes: results in 213,380 individuals from the cvMOBIUS2 registry - Satoshi Shoji; Nishant P. Shah; Peter Shrader; Laine E. Thomas; Jonathan D. Arnold; Nafeesa N. Dhalwani; Neena A. Thomas; Bethany Kalich; Elisa L. Priest; Mahanaz Syed; Cezary Wójcik; Eric D. Peterson; et al. (American Journal of Preventive Cardiology)
Objective: Lowering lipid to reach guideline-indicated goals significantly reduces cardiovascular outcomes in very-high-risk (VHR) patients with atherosclerotic cardiovascular disease (ASCVD) and type 2 diabetes (DM2). How well VHR patients currently achieve these goals in community practice is unknown. Methods: VHR patients with ASCVD and DM2 were identified across 14 US healthcare systems using electronic health records between 1/1/2021–12/31/2022. Achievement of guideline-based lipid goals was determined according to the 2018 AHA/ACC/Multisociety guideline, defined as either having a low-density lipoprotein-cholesterol <70 mg/dL or receiving maximal lipid-lowering therapy (i.e., on a PCSK9i monoclonal antibody). Multivariable logistic regression was used to evaluate factors associated with the achievement of these goals. Results: Among 213,380 eligible patients (median age 71.0 years, 42 % women), 51.8 % achieved guideline-based lipid goals. Female sex (odds ratio [OR], 0.64; 95 % confidence interval [CI], 0.61–0.66), Black race (OR, 0.67; 95 % CI, 0.63–0.72 vs white race), and those on Medicaid (OR, 0.92; 95 % CI, 0.86–0.97 vs Medicare) were associated with a lower likelihood of achieving guideline-based lipid goals. Overall, 76.0 % of patients were on statin, 40.5 % were on a high-intensity statin and only 5.8 % were on a statin in combination with ezetimibe or a PCSK9i monoclonal antibody. Conclusion: Almost half of all VHR patients with ASCVD and DM2 do not achieve current guideline lipid goals. Women, Black individuals, and those on Medicaid were significantly less likely to achieve these goals relative to their counterparts. Further targeted quality improvement interventions are needed to improve the equitable achievement of guideline-based lipid goals.